Aluminum salt lithium adsorbent as well as preparation method and application thereof

By grafting functional silane coupling agent on aluminum salt lithium adsorbent powder, vinyl modified aluminum salt lithium adsorbent is solved, and the problem of high powder loss and dissolution rate during recycling of aluminum-based adsorbent is achieved. Adsorbent with stability and high hydrophilic properties, suitable for lithium extraction of salt lake brine.

CN119140065AActive Publication Date: 2024-12-17TIANQI LITHIUM SHEHONG CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411294247.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

The existing aluminum-based lithium adsorbents have problems of high powder loss and dissolution rate during recycling, which affects their industrial application efficiency.

Method used

By grafting a functional silane coupling agent on the aluminum salt lithium adsorbent powder, cross-linking reaction is performed using a vinyl group-containing silane coupling agent, a hydrophilic group-containing silane coupling agent and a thiol compound to form a vinyl-modified compound. Aluminum salt lithium adsorbent increases its hydrophilic properties and three-dimensional network structure, and improves cyclic stability.

Benefits of technology

The cycle stability and hydrophilic properties of aluminum-based adsorbents are significantly improved, the dissolution rate of powder adsorbents is reduced, the loss of adsorbents is avoided, and the high-strength porous structure is formed, which extends the service life of adsorbents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140065A_ABST
    Figure CN119140065A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum salt lithium adsorbent and a preparation method and application thereof, and relates to the technical field of salt lake lithium extraction. According to the aluminum salt lithium adsorbent, a functional silane coupling agent is grafted on aluminum salt adsorbent powder, and in the preparation process, a vinyl-containing silane coupling agent is used for modifying an aluminum salt lithium adsorbent material to obtain a vinyl modified aluminum salt lithium adsorbent; a vinyl modified aluminum salt lithium adsorbent, a silane coupling agent with a hydrophilic group, a cross-linking agent and a sulfhydryl compound are mixed for reaction, the sulfhydryl compound contains carboxyl, and carboxyl negative charge functional groups and anions in brine generate repulsive interaction, so that blockage of the aluminum salt lithium adsorbent by high-valence anions in a solution is prevented, poisoning of the aluminum salt lithium adsorbent is avoided, and the service life of the aluminum salt lithium adsorbent is prolonged. And the hydrophilic performance can also be improved. The aluminum salt lithium adsorbent has good stability, the stability comprises high strength of granulated adsorbent particles, the solution loss rate of the powder adsorbent is reduced, meanwhile, a porous high-hydrophilicity internal structure is obtained, and the cycling stability of the porous high-hydrophilicity internal structure is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium extraction from salt lakes, and in particular to an aluminum salt lithium adsorbent and a preparation method and application thereof. Background Art

[0002] With the widespread application of electronic products and the rapid development of new energy vehicles, the demand for lithium resources has increased significantly. It is predicted that by 2030, there will be a very large gap in global lithium demand and a serious shortage of supply. Global lithium resources can be divided into two categories: salt lake and ore resources, of which lithium ore reserves in salt lakes account for more than 70%. Extracting lithium from salt lake brine has become an important direction for lithium resource production. To date, a variety of methods have been used to extract lithium from salt lake brine, such as precipitation, extraction, membrane separation, calcination leaching and adsorption. Among them, the adsorption method is considered to be one of the most promising technologies for extracting lithium from salt lake brine due to its cost-effectiveness and environmentally friendly advantages. High-performance adsorbents are the key factor for efficient lithium extraction by adsorption.

[0003] At present, the adsorbents prepared are divided into manganese adsorbents, titanium adsorbents and aluminum adsorbents, and the prepared adsorbents are all in powder form. Most of the powder adsorbents will lose powder during the recycling process, resulting in limited industrial applications. Manganese adsorbents and titanium adsorbents require acid for lithium deintercalation, which will further increase the loss of adsorbents. Aluminum adsorbents can deintercalate lithium without acid and have the advantages of no elution damage, making them more suitable adsorbents for lithium extraction from salt lakes.

[0004] Improving the morphology of powdered adsorbents through granulation, film making, foaming, membrane electrode method and other molding methods can effectively avoid powder loss and improve the recycling rate of adsorbents. Among them, granulation is the simplest and most commonly used molding method. Granulation usually involves directly mixing the adsorbent powder precursor with a binder, or repeatedly molding the precursor in a polymer solution through a cross-linking reaction to obtain a granular adsorbent. However, the performance of the adsorbent applied to actual salt lake brine will be reduced after granulation, because the binder or polymer itself is only physically entangled with the adsorbent powder or has weak intermolecular forces, hydrogen bond interactions, etc., which will cause the particles to break and swell during the recycling process, resulting in the loss of the adsorbed effective ingredients. In addition, granulation molding requires a complex process to prepare high-performance adsorbent particles.

[0005] Therefore, there is an urgent need to improve the preparation process of aluminum salt adsorbents in order to improve the cyclic stability of aluminum-based adsorbents and reduce the dissolution rate of powdered adsorbents.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The purpose of the present invention is to provide an aluminum salt lithium adsorbent and a preparation method and application thereof, aiming to improve the cyclic stability of the aluminum adsorbent and reduce the dissolution rate of the powder adsorbent.

[0008] The present invention is achieved in that:

[0009] In a first aspect, the present invention provides an aluminum salt lithium adsorbent, comprising an aluminum salt adsorbent powder, on which a functional silane coupling agent is grafted;

[0010] The preparation process of the aluminum salt lithium adsorbent includes: modifying the aluminum salt lithium adsorbent material with a vinyl-containing silane coupling agent to obtain a vinyl-modified aluminum salt lithium adsorbent, and mixing the vinyl-modified aluminum salt lithium adsorbent, a silane coupling agent with a hydrophilic group, a crosslinking agent and a mercapto compound for reaction;

[0011] The mercapto compound contains a carboxyl group; the hydrophilic group is selected from at least one of an amino group, a hydroxyl group and an epoxy group.

[0012] In an optional embodiment, in the aluminum salt lithium adsorbent, the mass proportion of the carboxyl group is 10%-40%.

[0013] In an optional embodiment, the aluminum salt lithium adsorbent material is selected from at least one of LiCl·Al(OH)3·nH2O and Li2SO4·Al(OH)3·nH2O;

[0014] Preferably, the vinyl-containing silane coupling agent is at least one selected from triethoxyvinylsilane, triacetoxyvinylsilane, methylvinyldimethoxysilane, vinyltrimethoxysilane and allyltrimethoxysilane.

[0015] In an optional embodiment, the mercapto compound is selected from at least one of 3-mercaptopropionic acid, mercaptosuccinic acid, 2-mercaptopropionic acid, 6-mercaptohexanoic acid, 12-mercaptododecanoic acid, 11-mercaptoundecanoic acid and 12-mercaptododecylphosphonic acid;

[0016] Preferably, the silane coupling agent with a hydrophilic group is selected from at least one of 3-piperazinylpropylmethyldimethoxysilane, 3-(2-aminoethylamino)propylmethyldimethylsilane, (3-aminopropyl)triethoxysilane, propionic acid trimethoxysilane, (3-glycidylpropoxy)trimethoxysilane and 3-mercaptopropylmethyldimethoxysilane;

[0017] Preferably, the crosslinking agent is selected from at least one of 1,2-bistrimethoxysilylethane and 1,2-bis(triethoxysilyl)ethane.

[0018] In a second aspect, the present invention provides a method for preparing an aluminum salt lithium adsorbent according to any one of the aforementioned embodiments, comprising: modifying the aluminum salt lithium adsorbent material using a vinyl-containing silane coupling agent to obtain a vinyl-modified aluminum salt lithium adsorbent, and mixing the vinyl-modified aluminum salt lithium adsorbent, a silane coupling with a hydrophilic group, a crosslinking agent and a thiol compound for reaction.

[0019] In an optional embodiment, the preparation process of the vinyl-modified lithium aluminum salt adsorbent includes: mixing the lithium aluminum salt adsorbent material, the vinyl-containing silane coupling agent and the first solvent for reaction, controlling the reaction temperature to 60° C.-90° C., and the reaction time to 8 h-24 h;

[0020] Preferably, a vinyl-containing silane coupling agent and a first solvent are first mixed to obtain a vinyl silane coupling agent solution, and the aluminum salt lithium adsorbent material and the vinyl silane coupling agent solution are mixed and reacted, and the mass fraction of the vinyl silane coupling agent solution is controlled to be 1%-12%;

[0021] Preferably, the mass ratio of the aluminum salt lithium adsorbent material to the vinyl-containing silane coupling agent is 1:(0.1-0.4);

[0022] Preferably, the particle size of the aluminum salt lithium adsorbent material is 200 mesh to 1200 mesh;

[0023] Preferably, the first solvent is a mixture of water and a first organic solvent, and the mass fraction of water in the first solvent is 5%-20%; more preferably, the first organic solvent is selected from at least one of anhydrous ethanol, methanol, isopropanol, propanol, glycerol, N-methylpyrrolidone and dimethyl sulfoxide.

[0024] In an optional embodiment, the preparation process of the vinyl-modified aluminum salt lithium adsorbent further includes: after the reaction of the aluminum salt lithium adsorbent material and the vinyl-containing silane coupling agent is completed, solid-liquid separation is performed to obtain a solid material, and the solid material is washed and dried.

[0025] In an optional embodiment, the vinyl-modified lithium aluminum salt adsorbent, the second solvent, the thiol compound, the crosslinking agent and the silane coupling agent with a hydrophilic group and the initiator are mixed and reacted, and the reaction temperature is controlled to be 60° C.-90° C., and the reaction time is 12 h-24 h;

[0026] Preferably, the mass ratio of the vinyl-modified aluminum salt lithium adsorbent to the mercapto compound is 1:(0.05-0.2);

[0027] Preferably, the initiator is selected from at least one of azobisisobutyronitrile and benzoyl peroxide, and the mass ratio of the initiator to the thiol compound is (0.5-2.0):100;

[0028] Preferably, the mass ratio of the vinyl-modified aluminum salt lithium adsorbent to the cross-linking agent is 1:(0.1-0.4);

[0029] Preferably, the mass ratio of the vinyl-modified lithium aluminum salt adsorbent to the silane coupling agent with a hydrophilic group is 1:(0.1-0.4).

[0030] In an optional embodiment, the vinyl-modified lithium aluminum salt adsorbent and the second solvent are mixed, and then mixed with the mercapto compound, the crosslinking agent, the silane coupling agent with a hydrophilic group and the initiator, and heated to react;

[0031] Preferably, the second solvent is a mixture of water and a second organic solvent, and the mass fraction of water in the second solvent is 5%-20%; more preferably, the second organic solvent is selected from at least one of anhydrous ethanol, methanol, isopropanol, propanol, glycerol, N-methylpyrrolidone and dimethyl sulfoxide;

[0032] Preferably, after the vinyl-modified aluminum salt lithium adsorbent, the mercapto compound and the silane coupling agent with a hydrophilic group are reacted, the stirring time is 2h-6h and then extrusion molding is performed, followed by activation;

[0033] More preferably, the activation comprises: drying the formed material;

[0034] Alternatively, the activation includes: soaking the formed material in a solvent and then drying it.

[0035] In a third aspect, the present invention provides a method for extracting lithium from salt lake brine, using any of the aluminum salt lithium adsorbents in the aforementioned embodiments or an aluminum salt lithium adsorbent prepared by any of the preparation methods in the aforementioned embodiments to adsorb lithium-containing brine;

[0036] Preferably, after the adsorption is completed, lithium is desorbed with water to obtain delithium aluminum salt lithium adsorbent particles.

[0037] The present invention has the following beneficial effects: the aluminum salt lithium adsorbent provided by the present invention is grafted with a functional silane coupling agent on the aluminum salt adsorbent powder. In the preparation process, the aluminum salt lithium adsorbent material is first modified by a vinyl-containing silane coupling agent to obtain a vinyl-modified aluminum salt lithium adsorbent. The vinyl-modified aluminum salt lithium adsorbent, the silane coupling agent with a hydrophilic group, the crosslinking agent and the thiol compound are mixed and reacted. The thiol compound contains a carboxyl group, and the carboxyl negatively charged functional group produces a repulsive effect with the anions in the brine, preventing the high-valent anions in the solution from clogging the aluminum salt lithium adsorbent, avoiding its "poisoning", and increasing its hydrophilicity; the silane coupling agent containing a hydrophilic group further increases its hydrophilicity, which can avoid the loss of adsorption performance. The aluminum salt lithium adsorbent provided by the embodiment of the present invention has good stability, and the stability includes high strength of the granulated adsorbent particles, reducing the dissolution rate of the powder adsorbent, and obtaining a porous and highly hydrophilic internal structure and ensuring its cyclic stability.

[0038] During the preparation process, the strength between the molded particles is improved through the covalent bond of the cross-linking agent, which avoids their dissolution and enables them to have a three-dimensional spatial structure connection. Compared with the traditional "film pasting" process of adding a binder, the aluminum salt lithium adsorbent provided in the embodiment of the present invention will not cause the deactivation of the adsorption sites, thereby achieving the purpose of improving the cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0040] Figure 1 A process flow chart of a method for preparing an aluminum salt lithium adsorbent provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0042] The present invention provides a method for preparing an aluminum salt lithium adsorbent, comprising: Figure 1 The preparation method of the hydrophilic three-dimensional network porous aluminum salt lithium adsorbent comprises the following steps:

[0043] S1. Preparation of vinyl-modified aluminum salt lithium adsorbent

[0044] A vinyl-modified aluminum salt lithium adsorbent is obtained by modifying the aluminum salt lithium adsorbent material with a vinyl-containing silane coupling agent. A vinyl-containing silane coupling agent is combined with the aluminum salt lithium adsorbent powder material. The vinyl-containing silane coupling agent acts as a "molecular bridge" to facilitate the introduction of other groups in subsequent polymerization.

[0045] In some embodiments, the preparation process of the vinyl-modified lithium aluminum salt adsorbent includes: mixing the lithium aluminum salt adsorbent material, the vinyl-containing silane coupling agent and the first solvent for reaction, the reaction temperature is 60° C.-90° C., and the reaction time is 6 h-24 h. The reaction temperature and time are adjusted to allow the reaction to proceed fully.

[0046] Specifically, the reaction temperature of the aluminum salt lithium adsorbent powder material and the vinyl-containing silane coupling agent can be 60°C, 70°C, 80°C, 90°C, etc., and the reaction time can be 6h, 10h, 16h, 20h, 24h, etc.

[0047] In some embodiments, the aluminum salt lithium adsorbent material is selected from at least one of LiCl·Al(OH)3·nH2O and Li2SO4·Al(OH)3·nH2O. The aluminum salt lithium adsorbent material can be any one of the above or a mixture of two of them. The above aluminum salt lithium adsorbent materials are all self-synthesized materials.

[0048] Specifically, the reference for the preparation process of LiCl·Al(OH)3·nH2O is: Zhang Wending "Synthesis and Performance Research of Aluminum Salt Lithium Adsorbent" [D].

[0049] Specifically, the preparation process reference of Li2SO4·Al(OH)3·nH2O is: Liu X, Zhong M, Chen X, et al. Enriching lithium and separating lithium to magnesium from sulfate typesalt lake brine-Science Direct[J].2020.105247-105264.

[0050] Further, the particle size of the aluminum salt lithium adsorbent material is 200 mesh-1200 mesh, such as 200 mesh, 600 mesh, 900 mesh, 1200 mesh, etc. The aluminum salt lithium adsorbent powder material can be crushed as needed to prevent the particle size of the aluminum salt lithium adsorbent powder material from being too large, which affects its full contact with the vinyl silane coupling agent.

[0051] In some embodiments, the vinyl-containing silane coupling agent is selected from at least one of triethoxyvinylsilane, triacetoxyvinylsilane, methylvinyldimethoxysilane, vinyltrimethoxysilane and allyltrimethoxysilane. The vinyl-containing silane coupling agent can be any one or more of the above, all of which can achieve modification of the aluminum salt lithium adsorbent material.

[0052] Furthermore, the mass ratio of the aluminum salt lithium adsorbent material and the vinyl-containing silane coupling agent is controlled to be 1:(0.1-0.4), such as 1:0.1, 1:0.2, 1:0.3, 1:0.4, etc. By adjusting the mass ratio of the aluminum salt lithium adsorbent material and the vinyl-containing silane coupling agent, the amount of vinyl introduced is controlled, so that the amount of mercapto compound introduced is controlled.

[0053] In the actual operation process, the vinyl-containing silane coupling agent and the first solvent can be evenly mixed to obtain a vinyl silane coupling agent solution, and then the aluminum salt lithium adsorbent material is added to the vinyl silane coupling agent solution, fully stirred and dispersed, and the temperature is raised to react. By adjusting the amount of the first solvent, the mass fraction of the vinyl silane coupling agent solution is controlled to be 1%-12%, such as 1wt%, 2wt%, 4wt%, 8wt%, 10wt%, 12wt%, etc. Under this concentration condition, the aluminum salt lithium adsorbent powder can be grafted with a suitable vinyl group.

[0054] Furthermore, the first solvent is a mixture of water and a first organic solvent, and the mass fraction of water in the first solvent is 5%-20%, such as 5%, 10%, 15%, 20%, etc. Within this concentration range, the silane coupling agent containing vinyl groups can be fully hydrolyzed, so that the silane coupling agent containing vinyl groups fully reacts.

[0055] In some embodiments, the first organic solvent is selected from at least one of anhydrous ethanol, methanol, isopropanol, propanol, glycerol, N-methylpyrrolidone and dimethyl sulfoxide, and the first organic solvent can be any one or more of the above.

[0056] It should be noted that, during the reaction, since the solvent is a mixture of water and an organic solvent, it is conducive to the hydrolysis of the vinyl silane coupling agent. The silane coupling agent containing vinyl groups has a highly reactive hydroxyl group, which can undergo a dehydration condensation reaction with the hydroxyl groups on the surface of the aluminum salt lithium adsorbent. The vinyl silane coupling agent acts as a "molecular bridge", which is convenient for the subsequent grafting and polymerization of thiol compounds, and is conducive to the construction of a three-dimensional network porous structure.

[0057] In some embodiments, the preparation process of the vinyl-modified aluminum salt lithium adsorbent further includes: after the reaction of the aluminum salt lithium adsorbent material and the vinyl-containing silane coupling agent is completed, solid-liquid separation is performed to obtain a solid material, and the solid material is washed and dried. The method of solid-liquid separation is not limited, and can be suction filtration, centrifugation, spray drying, etc.; the method of washing is not limited, and can be leaching or stirring washing, etc., and then the washing reagent is removed by drying. For example, short-chain organic alcohols (such as anhydrous ethanol) can be used for washing, which can further accelerate drying.

[0058] S2. Preparation of hydrophilic three-dimensional network porous structure aluminum salt lithium adsorbent particles

[0059] The vinyl-modified aluminum salt lithium adsorbent prepared in step S1, the carboxyl-containing thiol compound, the silane coupling agent with a hydrophilic group and the crosslinking agent are mixed and reacted. The silane coupling agent containing a vinyl group is combined with the aluminum salt lithium adsorbent powder material, and the silane coupling agent containing a vinyl group acts as a "molecular bridge"; the crosslinking agent is combined with the aluminum salt lithium adsorbent powder in the form of a covalent bond to form a three-dimensional porous structure; the silane coupling agent containing a hydrophilic functional group further increases the hydrophilicity of the aluminum adsorbent; the thiol compound reacts with the modified aluminum salt lithium adsorbent to further achieve excellent stability.

[0060] In some embodiments, a vinyl-modified lithium aluminum salt adsorbent, a second solvent, a thiol compound, a crosslinking agent, and a silane coupling agent with a hydrophilic group and an initiator are mixed and reacted. During the reaction, the thiol compound and the vinyl functional group react, and the crosslinking agent and the silane coupling agent containing a hydrophilic group are hydrolyzed to produce highly reactive hydroxyl groups that react with the hydroxyl groups on the surface of the lithium aluminum salt adsorbent to form a hydrophilic three-dimensional network crosslinked structure.

[0061] In some embodiments, the polymerization reaction temperature is controlled to be 60°C-90°C, such as 60°C, 70°C, 80°C, 90°C, etc.; the polymerization reaction time is 12h-24h, such as 12h, 14h, 18h, 22h, 24h, etc. The granulation molding requirements are met by adjusting the reaction time, and activation is performed after granulation to prepare a hydrophilic three-dimensional network porous structure aluminum salt lithium adsorbent particle.

[0062] In the actual operation process, the vinyl-modified aluminum salt lithium adsorbent and the second solvent are first mixed, and then mixed with the thiol compound, the cross-linking agent, the silane coupling agent with a hydrophilic group and the initiator, and heated to react. No inert gas protection is required during the reaction, and it needs to be carried out in an open reaction container with oxygen to prevent the self-polymerization of the silane coupling agent and the cross-linking agent.

[0063] In some embodiments, the second solvent is a mixture of water and a second organic solvent, the second organic solvent is selected from at least one of anhydrous ethanol, methanol, isopropanol, propanol, glycerol, N-methylpyrrolidone and dimethyl sulfoxide, and the second organic solvent can be any one or more of the above. The mass fraction of water in the second solvent is 5%-20%, such as 5%, 10%, 15%, 20%, etc. Controlling the concentration of water within the above range can, on the one hand, make the silane coupling agent therein more easily hydrolyzed and promote the reaction; on the other hand, it can make the vinyl aluminum salt lithium adsorbent powder more evenly dispersed to achieve the requirement of uniform adsorption performance, and can be formed and granulated within this range.

[0064] In some embodiments, the thiol compound is selected from at least one of 3-mercaptopropionic acid, mercaptosuccinic acid, 2-mercaptopropionic acid, 6-mercaptohexanoic acid, 12-mercaptododecanoic acid, 11-mercaptoundecanoic acid and 12-mercaptododecylphosphonic acid, and the thiol compound can be any one or more of the above. The thiol compound reacts with the vinyl modified adsorbent to make its surface have a large number of carboxyl groups, which on the one hand improves the hydrophilicity, and on the other hand can make the adsorbent surface have carboxylic acid groups, which can ionize hydrogen ions in brine and become carboxyl groups with negative charges, which can repel high-valent anions in salt lake brine and improve the cyclic stability of the formed adsorbent. The mass ratio of the vinyl modified aluminum salt lithium adsorbent to the thiol compound is 1: (0.05-0.2), such as 1: 0.05, 1: 0.08, 1: 0.10, 1: 0.15, 1: 0.20, etc. The quality of the vinyl-modified lithium aluminum salt adsorbent and the mercapto compound should be controlled within the above-mentioned range so that the concentration of the lithium aluminum salt adsorbent particles is within a relatively low range, thereby ensuring the stability of the adsorbent and the formation of a three-dimensional porous structure.

[0065] In some embodiments, the crosslinking agent is selected from at least one of 1,2-bistrimethoxysilylethane and 1,2-bis(triethoxysilyl)ethane, and the crosslinking agent may be any one or a mixture of the above two. The mass ratio of the vinyl-modified aluminum salt lithium adsorbent to the crosslinking agent is 1:(0.1-0.4), such as 1:0.1, 1:0.2, 1:0.3, 1:0.4, etc. The amount of the crosslinking agent used is preferably within the above range, which can promote the polymerization reaction and facilitate the molding of the powder.

[0066] In some embodiments, the silane coupling agent with a hydrophilic group is selected from at least one of 3-piperazinylpropylmethyldimethoxysilane, 3-(2-aminoethylamino)propylmethyldimethylsilane, (3-aminopropyl)triethoxysilane, propionic acid trimethoxysilane, (3-glycidylpropoxy)trimethoxysilane and 3-mercaptopropylmethyldimethoxysilane, and the silane coupling agent with a hydrophilic group can be any one or more of the above. The mass ratio of the vinyl-modified aluminum salt lithium adsorbent to the silane coupling agent with a hydrophilic group is 1: (0.1-0.4), such as 1: 0.1, 1: 0.2, 1: 0.3, 1: 0.4, etc. The amount of the silane coupling agent is preferably within the above range, which can significantly increase the hydrophilicity of the product.

[0067] In some embodiments, the initiator is selected from at least one of azobisisobutyronitrile and benzoyl peroxide, and the initiator can be any one or a mixture of the above two. The mass ratio of the initiator to the thiol compound is (0.5-2.0):100, such as 0.5:100, 1.0:100, 1.5:100, 2.0:100, etc. The initiator mainly initiates the reaction of the vinyl group and the thiol group, and the amount of the initiator in the above range can promote the polymerization reaction.

[0068] Further, after the polymerization reaction of the vinyl-modified aluminum salt lithium adsorbent, the thiol compound and the silane coupling agent with a hydrophilic group is completed, the stirring time is 2h-6h, and the molding granulator can be used to complete the molding. If the stirring time is too short, it is not easy to react, and if the time is too long, subsequent molding granulation will be difficult. Specifically, the stirring time after the reaction can be 2h, 3h, 4h, 5h, 6h, etc. Specifically, the molding process can be extruded by a molding machine such as a granulator or an extruder-rounding machine.

[0069] Furthermore, the molding is directly activated, and the activation method can be drying or soaking-drying. The reagent used for soaking can be water or organic solvent, etc., and the unreacted solvent and other raw materials are removed by drying to form a porous structure. The molded particles are cylindrical with a particle size of 1 mm or spherical with a particle size of 0.2-2 mm.

[0070] The embodiment of the present invention provides an aluminum salt lithium adsorbent, including aluminum salt adsorbent powder, on which a functional silane coupling agent is grafted, and the aluminum salt adsorbent powder can be prepared by the preparation method provided by the embodiment of the present invention.

[0071] It should be noted that the thiol compound bound to the vinyl silane coupling agent contains a carboxyl group, which can generate charge effects with anions in the brine to prevent the "poisoning" phenomenon of the aluminum salt lithium adsorbent. Moreover, the thiol compound is based on the surface of the aluminum salt lithium adsorbent powder material, which is beneficial to the formation of its three-dimensional network structure after molding. The formation of the three-dimensional network structure mainly relies on the connection effect of the cross-linking agent. The aluminum salt lithium adsorbent powder is directly combined by covalent bonds and will not adhere to the adsorbent surface to cause blockage of its active points, thereby ensuring the adsorption performance of the adsorbent powder, improving the strength after molding, and increasing the cyclic stability of the aluminum salt lithium adsorbent.

[0072] In some embodiments, in the aluminum salt lithium adsorbent, the mass proportion of the carboxyl group is 10%-40%, such as 10%, 20%, 30%, 40%, etc.

[0073] It should be noted that the aluminum salt lithium adsorbent provided in the embodiment of the present invention has the following advantages: (1) The traditional adhesive "film pasting" method will lead to the covering of active adsorption points, the decrease of adsorption performance and the poor cycle stability. The aluminum salt lithium adsorbent powders provided in the embodiment of the present invention are connected by covalent bonds, forming a three-dimensional spatial network porous structure with higher strength and good stability; (2) The silane coupling agent containing hydrophilic groups increases its hydrophilicity after molding, increases its wettability and avoids the decrease of adsorption performance; (3) No more complicated granulation molding process is required; (4) The aluminum salt lithium adsorbent contains carboxylic acid groups, which can generate charge effects with anions in brine to avoid the "poisoning" of the aluminum salt lithium adsorbent.

[0074] An embodiment of the present invention provides a method for extracting lithium from salt lake brine, wherein the aluminum salt lithium adsorbent provided by the embodiment of the present invention is used to adsorb lithium-containing brine. By improving the aluminum salt lithium adsorbent, the cyclic stability of the aluminum salt lithium adsorbent can be significantly improved.

[0075] After the adsorption is completed by the aluminum salt lithium adsorbent provided by the embodiment of the present invention, the lithium can be directly desorbed by water without acid washing, and the de-lithium aluminum salt lithium adsorbent particles can be obtained by analysis with pure water. During the adsorption and analysis process, due to its strong hydrophilicity, the lithium ion exchange of the adsorbent is very easy.

[0076] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0077] Example 1

[0078] This embodiment provides a method for preparing an aluminum salt lithium adsorbent, and the specific steps are as follows:

[0079] (1) An aqueous solution containing 93 wt% of anhydrous ethanol is used as a solvent, a silane coupling agent solution of triethoxyvinylsilane with a concentration of 2 wt% is prepared, and LiCl·Al(OH)3·nH2O powder material (also known as aluminum salt lithium adsorbent powder (anion is Cl - )) The powder is crushed to 200 meshes by a high-speed pulverizer, a certain amount of aluminum salt lithium adsorbent powder is placed in a vinyl silane coupling agent solution and fully dispersed, and then reacted at 60°C for 6 hours. After the reaction, it is filtered and washed with anhydrous ethanol and dried to obtain vinyl-modified aluminum salt lithium adsorbent powder. The mass ratio of the aluminum salt lithium adsorbent powder to the vinyl-containing silane coupling agent is controlled to be 1:0.2.

[0080] (2) Using an aqueous solution containing 93 wt% of anhydrous ethanol as a solvent, the vinyl-modified aluminum salt lithium adsorbent obtained in step (1) and the solvent are mixed to control the solid-liquid ratio to be 1.2 g / mL. 3-Mercaptopropionic acid is used as a thiol compound, 1,2-bistrimethoxysilylethane is used as a crosslinking agent, 3-piperazinepropylmethyldimethoxysilane is used as a silane coupling agent containing a hydrophilic group, and azobisisobutyronitrile is used as an initiator. Then, the reaction is heated to 60°C for 12 hours, and the reaction is stirred for 2 hours after the reaction is completed. The mixture is used for molding, extrusion and granulation, and dried and activated (the drying temperature is 100°C and the drying time is 12 hours, the same below) to obtain hydrophilic three-dimensional network porous aluminum salt lithium adsorbent particles. Among them, the mass ratio of vinyl-modified aluminum salt lithium adsorbent powder to the thiol compound is 1:0.05, the mass of the cross-linking agent is 10% of the mass of the vinyl-modified aluminum salt lithium adsorbent powder (that is, the mass ratio of vinyl-modified aluminum salt lithium adsorbent powder to the cross-linking agent is 1:0.1), the mass of the initiator is 0.5% of the mass of the thiol compound, and the mass of the silane coupling agent containing a hydrophilic group is 10% of the mass of the vinyl-modified aluminum salt lithium adsorbent powder (that is, the mass ratio of vinyl-modified aluminum salt lithium adsorbent powder to the silane coupling agent containing a hydrophilic group is 1:0.1).

[0081] This embodiment also provides a method for extracting lithium from salt lake brine, the method is as follows: aluminum salt lithium adsorbent particles are placed in an adsorption column containing brine to adsorb lithium, and after the adsorption is completed, only the same amount of pure water is needed for analysis to complete the adsorption-analysis cycle of the aluminum salt lithium adsorbent particles, and the adsorption-analysis operation is repeated 50 times to measure its cyclic stability. The composition of the brine is as follows: magnesium ion 8.26g / L, sodium ion 19.25g / L, lithium ion 1.84g / L, chloride ion 20.13g / L, sulfate ion 40.02g / L.

[0082] Example 2

[0083] This embodiment provides a method for preparing an aluminum salt lithium adsorbent, and the specific steps are as follows:

[0084] (1) An aqueous solution containing 84 wt% of anhydrous methanol is used as a solvent to prepare a silane coupling agent solution of 8 wt% of vinyl trimethoxysilane, and Li2SO4·Al(OH)3·nH2O powder material is crushed to 600 meshes by a high-speed crusher, and a certain amount of aluminum salt lithium adsorbent powder is placed in the vinyl silane coupling agent solution and fully dispersed, and then reacted at 70° C. for 10 hours, and then filtered after the reaction, and washed and dried with anhydrous ethanol to obtain vinyl-modified aluminum salt lithium adsorbent powder. The mass ratio of aluminum salt lithium adsorbent powder to vinyl-containing silane coupling agent is controlled to be 1:0.3.

[0085] (2) Using an aqueous solution containing 84 wt% of anhydrous methanol as a solvent, the vinyl-modified aluminum salt lithium adsorbent obtained in step (1) and the solvent are mixed to control the solid-liquid ratio to be 1.2 g / mL. 2-Mercaptopropionic acid is used as a thiol compound, 1,2-bis(triethoxysilyl)ethane is used as a crosslinking agent, (3-aminopropyl)triethoxysilane is used as a silane coupling agent of a hydrophilic group, and benzoyl peroxide is added to the solution as an initiator, and then the reaction temperature is heated to 70°C for 14 hours, followed by stirring for 4 hours, and used for molding, extrusion and granulation. After drying and activation, hydrophilic three-dimensional network porous aluminum salt lithium adsorbent particles are obtained. The mass ratio of the vinyl-modified aluminum salt adsorbent powder to the thiol compound is 1:0.08, the mass of the crosslinking agent is 20% of the mass of the vinyl-modified aluminum salt lithium adsorbent powder, the mass of the initiator is 1% of the mass of the thiol compound, and the mass of the silane coupling agent containing a hydrophilic group is 20% of the mass of the aluminum salt lithium adsorbent powder.

[0086] This embodiment also provides a method for extracting lithium from salt lake brine, which is the same as that in Example 1.

[0087] Example 3

[0088] This embodiment provides a method for preparing an aluminum salt lithium adsorbent, and the specific steps are as follows:

[0089] (1) An aqueous solution containing 78 wt% of isopropanol is used as a solvent, and a silane coupling agent solution containing 10 wt% of allyltrimethoxysilane is prepared. LiCl·Al(OH)3·nH2O powder material is crushed to 900 meshes by a high-speed crusher. A certain amount of aluminum salt lithium adsorbent powder is placed in the vinyl silane coupling agent solution and fully dispersed, and then reacted at 80° C. for 16 hours. After the reaction, the mixture is filtered, washed with anhydrous isopropanol, and dried to obtain vinyl-modified aluminum salt lithium adsorbent powder. The mass ratio of the aluminum salt lithium adsorbent powder to the vinyl-containing silane coupling agent is controlled to be 1:0.4.

[0090] (2) Using an aqueous solution containing 78 wt% of isopropanol as a solvent, the vinyl-modified aluminum salt lithium adsorbent obtained in step (1) and the solvent are mixed to control the solid-liquid ratio to be 1.2 g / mL. 6-mercaptohexanoic acid is used as a thiol compound, 1,2-bistrimethoxysilylethane is used as a crosslinker, a silane coupling agent of trimethoxysilane propionate, and benzoyl peroxide is added to the solution as an initiator, and then the reaction temperature is heated to 80°C for 22 hours, followed by stirring for 6 hours, and used for molding, extrusion and granulation. After drying and activation, hydrophilic three-dimensional network porous aluminum salt lithium adsorbent particles are obtained. The mass ratio of the vinyl-modified aluminum salt adsorbent powder to the thiol compound is 1:0.15, the mass of the crosslinker is 30% of the mass of the vinyl-modified aluminum salt lithium adsorbent powder, the mass of the initiator is 2.0% of the mass of the thiol compound, and the mass of the silane coupling agent containing a hydrophilic group is 40% of the mass of the aluminum salt lithium adsorbent powder.

[0091] This embodiment also provides a method for extracting lithium from salt lake brine, which is the same as that in Example 1.

[0092] Example 4

[0093] This embodiment provides a method for preparing an aluminum salt lithium adsorbent, and the specific steps are as follows:

[0094] (1) Using an aqueous solution containing 68 wt% of N-methylpyrrolidone as a solvent, a silane coupling agent solution containing triacetoxyvinylsilane at a concentration of 12 wt% is prepared, and LiCl·Al(OH)3·nH2O powder material is crushed to 1200 meshes by a high-speed crusher, and a certain amount of aluminum salt lithium adsorbent powder is placed in the vinyl silane coupling agent solution and fully dispersed, and then reacted at 90° C. for 6 hours, and then filtered after the reaction, and washed and dried with anhydrous isopropanol to obtain vinyl-modified aluminum salt lithium adsorbent powder. The mass ratio of aluminum salt lithium adsorbent powder to vinyl-containing silane coupling agent is controlled to be 1:0.2.

[0095] (2) Using an aqueous solution containing 68 wt% of N-methylpyrrolidone as a solvent, the vinyl-modified aluminum salt lithium adsorbent obtained in step (1) and the solvent are mixed to control the solid-liquid ratio to be 1.2 g / mL. Add mercaptosuccinic acid as a thiol compound, 1,2-bis(triethoxysilyl)ethane as a crosslinker, 3-piperazinylpropylmethyldimethoxysilane as a silane coupling agent, and azobisisobutyronitrile as an initiator to the solution, and then heat the solution to 90°C for reaction for 24 hours, then stir for 2 hours, and use it for molding, extrusion and granulation. After drying and activation, hydrophilic three-dimensional network porous aluminum salt lithium adsorbent particles are obtained. The mass ratio of the vinyl-modified aluminum salt adsorbent powder to the thiol compound is 1:0.2, the mass of the crosslinker is 40% of the mass of the vinyl-modified aluminum salt lithium adsorbent powder, the mass of the initiator is 2.0% of the mass of the thiol compound, and the mass of the silane coupling agent containing a hydrophilic group is 40% of the mass of the aluminum salt lithium adsorbent powder.

[0096] This embodiment also provides a method for extracting lithium from salt lake brine, which is the same as that in Example 1.

[0097] Example 5

[0098] The only difference between this embodiment and Embodiment 1 is that the aluminum salt lithium adsorbent powder is a mixed powder of LiCl·Al(OH)3·nH2O and Li2SO4·Al(OH)3·nH2O, and the mass ratio of LiCl·Al(OH)3·nH2O to Li2SO4·Al(OH)3·nH2O is 1:1.

[0099] Example 6

[0100] The only difference between this embodiment and embodiment 2 is that the reaction time of step (1) and step (2) is 24 hours.

[0101] Example 7

[0102] The only difference between this embodiment and embodiment 4 is that the modification temperature in step (1) and the polymerization reaction temperature in step (2) are both 60°C.

[0103] Example 8

[0104] The only difference from Example 1 is that in step (1), LiCl·Al(OH )3 The nH2O powder material is replaced with an equal amount of Li2SO4·Al(OH)3·nH2O powder material.

[0105] Example 9

[0106] The only difference from Example 1 is that the amount of LiCl·Al(OH)3·nH2O powder material used in step (1) is 0.6 times the amount of powder used in Example 1.

[0107] Comparative Example 1

[0108] The difference between the comparative example and Example 1 is that the comparative example 1 directly uses aluminum salt lithium adsorbent powder to extract lithium from brine without modification and polymerization reaction molding and granulation process.

[0109] Comparative Example 2

[0110] The preparation process and dosage of Comparative Example 2 are consistent with those of step (1) of Example 1, except that no crosslinking agent or hydrophilic group silane coupling agent is added in step (2), and only the product obtained in step (1) is reacted with a mercapto compound (consistent with the dosage in step (2)) for granulation.

[0111] Comparative Example 3

[0112] The difference between Comparative Example 3 and Example 1 is that only the aluminum salt lithium adsorbent is formed and granulated by a conventional method. The specific method is as follows: take the unmodified aluminum salt lithium adsorbent powder consistent with Example 1 (i.e., the LiCl·Al(OH)3·nH2O powder material in Example 1), mix it with the binder polyvinyl chloride (PVC) powder and the organic solvent N-methylpyrrolidone in a mass ratio of 1:0.3:0.2, and use the same extruder to granulate.

[0113] Comparative Example 4

[0114] The only difference between Comparative Example 4 and Comparative Example 3 is that the unmodified aluminum salt lithium adsorbent powder consistent with Example 1 is taken, mixed with the adhesive polyvinyl chloride (PVC) powder and the organic solvent N-methylpyrrolidone in a mass ratio of 1:0.4:0.4, and granulated using the same extruder.

[0115] Comparative Example 5

[0116] The only difference from Example 1 is that no thiol compound is added in step (2).

[0117] Comparative Example 6

[0118] The only difference from Example 1 is that no hydrophilic group silane coupling agent is added in step (2).

[0119] Test Example 1

[0120] The desorption capacity, desorption capacity retention rate and hydrophilicity of the adsorbents prepared in the test examples and comparative examples are shown in Table 1.

[0121] Test method:

[0122] (1) Desorption capacity = (volume of analytical solution * Li concentration in analytical solution) / column volume * 0.46 (Li ratio in lithium oxide);

[0123] (2) Desorption capacity retention rate = desorption capacity at 50 cycles / desorption capacity at the beginning * 100%;

[0124] (3) Dissolution test: After 50 cycles of adsorption-desorption, the aluminum salt lithium adsorbent powder or particles of the above-mentioned embodiments and comparative examples were taken out, dried and weighed, and the aluminum salt lithium adsorbent particles were weighed after drying. Then, the dissolution rate of the aluminum salt lithium adsorbent was calculated. The calculation formula is as follows: Dissolution rate = m1 / m0*100%, where m1 is the dry weight after 50 cycles, and m0 is the initial dry weight.

[0125] (4) Hydrophilicity test: Place a sufficiently large droplet (50 μL) on the surface of the sample to be tested and record the droplet wetting time until no droplets are visible.

[0126] Table 1 Test results of adsorption performance, stability and hydrophilicity of adsorbents in Examples and Comparative Examples

[0127]

[0128]

[0129] It can be seen from Table 1 that the hydrophilic three-dimensional network porous aluminum salt lithium adsorbent particles prepared in the embodiment of the present invention can significantly improve the stability of the aluminum salt lithium adsorbent particles after brine lithium extraction, including stable adsorption performance, cyclic stability, low dissolution loss, excellent hydrophilic performance, etc., and at the same time can prevent the "poisoning" phenomenon of high-valent anions.

[0130] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An aluminum salt lithium adsorbent, characterized in that: It comprises aluminum salt adsorbent powder, on which a functional silane coupling agent is grafted; The preparation process of the aluminum salt lithium adsorbent includes: modifying the aluminum salt lithium adsorbent material with a vinyl-containing silane coupling agent to obtain a vinyl-modified aluminum salt lithium adsorbent, and mixing the vinyl-modified aluminum salt lithium adsorbent, a silane coupling agent with a hydrophilic group, a crosslinking agent and a mercapto compound for reaction; The mercapto compound contains a carboxyl group; the hydrophilic group is selected from at least one of an amino group, a hydroxyl group and an epoxy group.

2. The aluminum salt lithium adsorbent according to claim 1, characterized in that In the aluminum salt lithium adsorbent, the mass proportion of the carboxyl group is 10%-40%.

3. The aluminum salt lithium adsorbent according to claim 1, characterized in that The aluminum salt lithium adsorbent material is selected from at least one of LiCl·Al(OH)3·nH2O and Li2SO4·Al(OH)3·nH2O; Preferably, the vinyl-containing silane coupling agent is at least one selected from triethoxyvinylsilane, triacetoxyvinylsilane, methylvinyldimethoxysilane, vinyltrimethoxysilane and allyltrimethoxysilane.

4. The aluminum salt lithium adsorbent according to claim 3, characterized in that The mercapto compound is selected from at least one of 3-mercaptopropionic acid, mercaptosuccinic acid, 2-mercaptopropionic acid, 6-mercaptohexanoic acid, 12-mercaptododecanoic acid, 11-mercaptoundecanoic acid and 12-mercaptododecylphosphonic acid; Preferably, the silane coupling agent with a hydrophilic group is selected from at least one of 3-piperazinylpropylmethyldimethoxysilane, 3-(2-aminoethylamino)propylmethyldimethylsilane, (3-aminopropyl)triethoxysilane, propionic acid trimethoxysilane, (3-glycidylpropoxy)trimethoxysilane and 3-mercaptopropylmethyldimethoxysilane; Preferably, the crosslinking agent is selected from at least one of 1,2-bistrimethoxysilylethane and 1,2-bis(triethoxysilyl)ethane.

5. A method for preparing the aluminum salt lithium adsorbent according to any one of claims 1 to 4, characterized in that: include: The aluminum salt lithium adsorbent material is modified by using a vinyl-containing silane coupling agent to obtain the vinyl-modified aluminum salt lithium adsorbent, and the vinyl-modified aluminum salt lithium adsorbent, a silane coupling agent with a hydrophilic group, a crosslinking agent and a mercapto compound are mixed and reacted.

6. The preparation method according to claim 5, characterized in that: The preparation process of the vinyl-modified aluminum salt lithium adsorbent comprises: mixing an aluminum salt lithium adsorbent material, a vinyl-containing silane coupling agent and a first solvent for reaction, controlling the reaction temperature to be 60° C.-90° C., and the reaction time to be 8 h-24 h; Preferably, the vinyl-containing silane coupling agent and the first solvent are first mixed to obtain a vinyl silane coupling agent solution, and the aluminum salt lithium adsorbent material and the vinyl silane coupling agent solution are mixed and reacted, and the mass fraction of the vinyl silane coupling agent solution is controlled to be 1%-12%; Preferably, the mass ratio of the aluminum salt lithium adsorbent material to the vinyl-containing silane coupling agent is 1:(0.1-0.4); Preferably, the particle size of the aluminum salt lithium adsorbent material is 200 mesh to 1200 mesh; Preferably, the first solvent is a mixture of water and a first organic solvent, and the mass fraction of water in the first solvent is 5%-20%; more preferably, the first organic solvent is selected from at least one of anhydrous ethanol, methanol, isopropanol, propanol, glycerol, N-methylpyrrolidone and dimethyl sulfoxide.

7. The preparation method according to claim 6, characterized in that: The preparation process of the vinyl-modified aluminum salt lithium adsorbent also includes: after the reaction of the aluminum salt lithium adsorbent material and the vinyl-containing silane coupling agent is completed, solid-liquid separation is performed to obtain a solid material, and the solid material is washed and dried.

8. The preparation method according to claim 5, characterized in that: The vinyl-modified lithium aluminum salt adsorbent, the second solvent, the thiol compound, the crosslinking agent and the silane coupling and initiator with a hydrophilic group are mixed and reacted, and the reaction temperature is controlled to be 60° C.-90° C. and the reaction time is 12 h-24 h; Preferably, the mass ratio of the vinyl-modified aluminum salt lithium adsorbent to the thiol compound is 1:(0.05-0.2); Preferably, the initiator is selected from at least one of azobisisobutyronitrile and benzoyl peroxide, and the mass ratio of the initiator to the thiol compound is (0.5-2.0):100; Preferably, the mass ratio of the vinyl-modified aluminum salt lithium adsorbent to the cross-linking agent is 1:(0.1-0.4); Preferably, the mass ratio of the vinyl-modified lithium aluminum salt adsorbent to the silane coupling agent with a hydrophilic group is 1:(0.1-0.4).

9. The preparation method according to claim 8, characterized in that: The vinyl-modified lithium aluminum salt adsorbent and the second solvent are mixed, and then mixed with the mercapto compound, the crosslinking agent, the silane coupling agent with a hydrophilic group and the initiator, and heated to react; Preferably, the second solvent is a mixture of water and a second organic solvent, and the mass fraction of water in the second solvent is 5%-20%; more preferably, the second organic solvent is selected from at least one of anhydrous ethanol, methanol, isopropanol, propanol, glycerol, N-methylpyrrolidone and dimethyl sulfoxide; Preferably, after the vinyl-modified lithium aluminum salt adsorbent, the mercapto compound and the silane coupling agent with a hydrophilic group have completed the reaction, the stirring time is 2h-6h and then extrusion molding is performed, followed by activation; More preferably, the activation comprises: drying the formed material; Alternatively, the activation comprises: soaking the formed material in a solvent and then drying it.

10. A method for extracting lithium from salt lake brine, characterized in that: Adsorbing lithium-containing brine using the aluminum salt lithium adsorbent described in any one of claims 1 to 4 or the aluminum salt lithium adsorbent prepared by the preparation method described in any one of claims 5 to 9; Preferably, after the adsorption is completed, lithium is desorbed with water to obtain delithium aluminum salt lithium adsorbent particles.

Citation Information

Patent Citations

  • Porous lithium adsorbent and preparation method and application thereof

    CN114917862A

  • Adhesive for salt lake lithium extraction adsorbent, adsorbent and preparation method thereof

    CN117965115A

  • Montmorillonite-based composite lithium ion adsorbent and preparation method thereof

    CN118403607A

  • Binder emulsion, preparation method of binder emulsion, coating slurry, lithium ion battery diaphragm and preparation method of lithium ion battery diaphragm

    CN120077513A

  • Sorbent for lithium extraction

    US8753594B1